Respuesta :
Answer:
The term that completes the product so that it is the difference of squares is 3.
Step-by-step explanation:
The term that completes the product so that it is the difference of squares is 3.
Reason:
(-5x-3)(-5x+3)=(5x)^2 - (3)^2
A difference of squares is the difference of two squared terms.
We have
a^2 - b^2
We can factorize the difference of squared terms like this:
a^2-b^2 = (a+b)(a-b)
We have (-5x-3)(-5x+3)
Lets prove it:
(-5x-3)(-5x+3) = (-5x*-5x)+(-5x*3)+(-3*-5x)+(-3*3)
(-5x-3)(-5x+3) = 25x^2+(-15x)+(15x)+(-9)
(-5x-3)(-5x+3) = 25x^2-15x+15x-9
(-5x-3)(-5x+3) = 25x^2-9
(-5x-3)(-5x+3) = (5x)^2 - (3)^2
we have that the obtained expression is a difference of squares.
Therefore the correct option is 3. The term that completes the product so that it is the difference of squares is 3 ....